The Relationship between Motivational Structure, Mental Health and Attitude to Opiate Substances in University Students - Ali akbar Soliemanian; Abbas Firouzabadi (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: This study was carried out with the aim of evaluating the relationship between motivational structure, mental health and attitude to opiate substances in a sample of North-Khorasan's university students. Method: In a descriptive cross-sectional study, 400 participants (200 males and 200 females) were selected by stratified random sampling of three universities of north khorasan. All participants completed the SCL-90-R, Personal Concerns Inventory and Attitude to Opiate Substances questionnaire. Findings: The results revealed that there was a significant difference between participants with maladaptive motivational structure and adaptive motivational structure on GSI and subscales of SCL-90-R. In addition, the comparison of two groups showed that participants with maladaptive motivational structure had significant more positive attitude to opiate Substances than participants with adaptive motivational structure. Conclusion: There is a significant relationship between motivational structure, mental health and attitude to opiate substances.